2019
DOI: 10.1007/s13205-018-1555-x
|View full text |Cite
|
Sign up to set email alerts
|

Effective production of keratinase by gellan gum-immobilised Alcaligenes sp. AQ05-001 using heavy metal-free and polluted feather wastes as substrates

Abstract: The ability of gellan gum-immobilised cells of the heavy metal-tolerant bacterium Alcaligenes sp. AQ05-001 to utilise both heavy metal-free and heavy metal-polluted feathers (HMPFs) as substrates to produce keratinase enzyme was studied. Optimisation of the media pH, incubation temperature and immobilisation parameters (bead size, bead number, gellan gum concentration) was determined for the best possible production of keratinase using the one-factor-at-a-time technique. The results showed that the immobilised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Improper disposal of such wastes also pose a great pollution threat apart from the direct health risk to humans and animals (due to possible transmission of pathogenic microbes). Proteases, especially the keratinases and collagenases are also playing pivotal role in the arena of waste management and pollution control by breaking down these problematic components (Bhagwat and Dange 2018 ; Razzaq et al 2019 ; Yusuf et al 2019 ). The keratinases (proteases, which are capable of degrading keratin) have been used for degradation of keratin in the waste materials, thus helping in the waste management.…”
Section: Introductionmentioning
confidence: 99%
“…Improper disposal of such wastes also pose a great pollution threat apart from the direct health risk to humans and animals (due to possible transmission of pathogenic microbes). Proteases, especially the keratinases and collagenases are also playing pivotal role in the arena of waste management and pollution control by breaking down these problematic components (Bhagwat and Dange 2018 ; Razzaq et al 2019 ; Yusuf et al 2019 ). The keratinases (proteases, which are capable of degrading keratin) have been used for degradation of keratin in the waste materials, thus helping in the waste management.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of Bacillus strains with keratinolytic activity prevailed over any other genus of bacteria . Valorisation of waste feathers [5,65,66,87] and the replacement of the traditional, highly polluting hide dehairing step used in the leather industry with a more environmentally friendly enzymatic step using keratinases [2,55,79,88] were the dominant themes of these papers.…”
Section: Microbial Degradation Of Keratinmentioning
confidence: 99%
“…Robinson and Tuovinen (1984) reported that Hg is soluble in lipids and can easily bind to proteins containing sulfhydryl groups in the cell membrane, as well as to enzymes, causing toxicity. Mercury toxicity to bioremediation activity can be reduced by the addition of metal immobilising agents (Yusuf et al, 2019). Ibrahim et al (2016) reported that immobilised Leifsonia sp.…”
Section: Effects Of Heavy Metal On Canola Oil Degradationmentioning
confidence: 99%